Fatores associados à periodontite agressiva em uma população do nordeste brasileiro: um estudo de corte transversal aninhado à coorte RPS - CHAVES, Cláudia Oliveira (2018)
Aggressive Periodontitis (AgP) is a rare disease associated with dental biofilm and genetic and immunoinflammatory host factors, and may be influenced by sociodemographic and behavioral factors. However, studies that investigated the AgP in Brazilian Northeast are scarce in the literature. The aim of this paper was to estimate the prevalence of AgP and possible factors associated to the disease in a population of teenagers of São Luís, Maranhão, Brazil. This is a cross-sectional study nested in the Ribeirão Preto, Pelotas, São Luís (RPS) birth cohort, consisting of 1570 adolescents of 18 and 19 years living in São Luís selected by probabilistic sampling that answered to questionnaires and were submitted to the periodontal clinical examination in 6 sites per tooth. The periodontal parameters investigated were: probing depth, clinical attachment loss, plaque index and bleeding on probing. Absolute and relative frequencies were used for sample description and robust Poisson regression to estimate associations of variables in crude and adjusted analyses. The significance level for null hypothesis rejection was 5% and the confidence interval was 95%. AgP prevalence was 13.06% e 8.34% corresponded to generalized AgP in sample. The disease was more frequent in brown adolescents, of middle socioeconomic class and significantly higher in males (64.39%). Means of the periodontal parameters evaluated were higher in the group with AgP and the molars were the most affected group of teeth (83.41%). Regression analysis showed that the infrequent use of dental floss (PR 1.16; IC95% 1.04-2.46; p=0,030) or never use it (PR 1.74; IC95% 1.14-2.66; p=0.009), to use mouthwash more frequently (PR 1.81; IC95% 1.02-3.22; p=0.042) and never have been to the dentist (PR1.84; IC95% 1.09-3.09; p=0.021) were positively associated with AgP and that daily brushing (PR 0.30; IC95% 0.15-0.61; p=0.001) had an inverse association. Socio-economic class and smoking were not associated to the disease in this study. It is concluded that the prevalence of AgP in this population was higher than those observed in the literature and that and that frequency of floss and mouthwash, daily brushing and date of the last visit to the dentist were associated factor with the disease